Elastic scattering analysis of p+40 Ca at incident energies from threshold to 48.4 MeV and nuclear matter radius - Ismail, A. (World Scientific Publishing Co. Pte Ltd, 2015)
Proton elastic scattering at various incident energies is one method to study nuclear density distributions and nuclear radii. Single folding potential describing the p-scattering on 40Ca over a broad energy range 9-48.4 MeV is constructed. The resulting potential does not need any renormalization to fit the measured elastic scattering angular distributions and total reaction cross-sections. Furthermore, correlation between volume integral and proton incident energy is discussed. Theoretical calculations are in a good agreement with existing experimental data. Â© 2015 World Scientific Publishing Company.